2015
DOI: 10.3897/jhr.46.5518
|View full text |Cite
|
Sign up to set email alerts
|

Protection against herbivory in the mutualism between Pseudomyrmex dendroicus (Formicidae) and Triplaris americana (Polygonaceae)

Abstract: Herbivory significantly impacts the growth and reproduction of plants. Many plants have developed ways to defend against herbivores and one common strategy is to associate with ants. In many ant-plant interactions, ants are known to protect their host. However, in the Neotropical ant-plant genus Triplaris, the benefits provided by associated ants have never been tested. Many Pseudomyrmex spp. ants are obligate inhabitants of Triplaris spp. trees. In this study, Triplaris americana was studied in association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In the case of host recognition, ants are known to respond to chemical cues from their hosts. They rapidly recruit in response to herbivory attacks [ 27 , 67 ] and queens select their host plant primarily based on chemical recognition [ 64 , 65 , 68 , 69 , 70 , 71 ]. Chemical analysis of myrmecophytic Macaranga showed that even closely related species, sharing the same ant partners, can have very different scent patterns and that foundress queens have the capacity to distinguish between different hosts [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of host recognition, ants are known to respond to chemical cues from their hosts. They rapidly recruit in response to herbivory attacks [ 27 , 67 ] and queens select their host plant primarily based on chemical recognition [ 64 , 65 , 68 , 69 , 70 , 71 ]. Chemical analysis of myrmecophytic Macaranga showed that even closely related species, sharing the same ant partners, can have very different scent patterns and that foundress queens have the capacity to distinguish between different hosts [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Triplaris - Pseudomyrmex interaction is a well-known case of myrmecophytism in the Neotropics and some ecological studies have addressed the interaction [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, although there has been some work done on the relationships between the Pseudomyrmex species associated with Triplaris [ 28 ], there has been no attempt to compare the phylogenetic framework of these two groups of organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ants belonging to the genus Pseudomyrmex possess venoms that rapidly subdue prey and effectively deter herbivores, suggesting that they contain both neurotoxic and cytotoxic compounds [9].…”
Section: Introductionmentioning
confidence: 99%
“…In myrmecophytic associations, ant-plants provide nesting space inside domatia, and in some cases, food rewards, while ants protect plants against herbivory, pathogens, and encroaching vegetation (Rico-Gray and Oliveira 2007 ; Mayer et al 2014 ; Sanchez and Bellota 2015 ). Myrmecophytism is widespread and very diverse in the Tropics where at least 100 different plant genera are inhabited by ant colonies (Davidson and McKey 1993 ; Chomicki and Renner 2015 ).…”
Section: Introductionmentioning
confidence: 99%